Is Human Papillomavirus Infection Among HIV-Infected Men in Kenya Underestimated?. (21st September 2018) - Mokua, Grace; Rogena, Emily; Kigondu, Christine; Rioki, Josephine; Ngayo, Musa Otieno
Abstract: Objectives: To detect the prevalence of HPV infection in urine samples among HIV-infected men attending CCC in a high-volume hospital in Kenya and to determine performance of molecular diagnosis against cytological evaluation in urine samples for the diagnosis of HPV infection among HIV-infected men attending CCC in a high-volume hospital in Kenya. Methods: Real-time PCR and cytomorphological evaluation. Results: HPV oncogenic types with real-time PCR = 25.3% and cytomorphological changes = 8.4%. The agreement of RT-PCR with cytology was fair (κ, 0.264). The carcinogenic HPV detection for PCR as reference, concordance, sensitivity, and specificity for cytology was 91.6%, 23.9%, and 96.8%, respectively. Conclusion: Prevalence of oncogenic HPV infection was high among HIV men; also, there was an increase in cytological grading, supporting the validity of urine sampling for evaluation.